The effect of enterprise risk management on firm value: evidence from Malaysian technology firms - Mohd. Hafizuddin Syah Bangaan Abdullah; Hawati Janor; Mohamad Abdul Hamid; Puan Yatim (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper aims to examine the relationship between ERM and firm value in Malaysia. In the past literature, ERM had been argued to increase firm value but empirical evidence shows mixed and inconclusive results. Using sample from 2004 to 2012, this paper furthers the analysis on the relationship between ERM and firm performance among technology firms in Malaysia. Indeed, technology industry is the fastest growing and a volatile industry, which requires continuous innovation. These make technology firms more prone to risk exposure. In analyzing this issue, dynamic panel data is employed to allow cross-sectional and time series analysis. Our results show that the implementation of ERM in the previous year has strong negative relationship with firm value at 1 percent significance level. It supports the argument that the effect of ERM is not immediately realized as well as entails high implementation cost. The findings provide useful input and insight in formulating new policy in relation to corporate governance, particularly ERM in Malaysia.